Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.21123/bsj.2020.17.3(suppl.).1103
|View full text |Cite
|
Sign up to set email alerts
|

Fat Mass and Obesity Association gene Polymorphism in PCOS Iraqi Women

Abstract: Polycystic syndrome (PCOS) is a considerable infertility disorder in adolescents and adult women in reproductive age. Obesity is a vigorous risk factor related to POCS.  This study aims to evaluate the association of obesity and PCOS by investigating several parameters including:  anthropological, biochemical (lipid profile, fasting blood sugar, glucose tolerance test, and hormone levels (LH, FSH, LH/FSH ratio, Estradiol2 and Testosterone),and genetic parameters (Fat mass and Obesity associated gene (FTO) poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…The frequency of G minor allele was 45.3% in the American population [23] compared to 60.53% in the PCOS group in the present study. Recently, in an Iraqi study evaluating the association of rs17817449 with obesity in PCOS women, the allele frequencies for T and G in PCOS women were, respectively, 48% and 52%, different from our findings [40].…”
Section: Discussioncontrasting
confidence: 99%
“…The frequency of G minor allele was 45.3% in the American population [23] compared to 60.53% in the PCOS group in the present study. Recently, in an Iraqi study evaluating the association of rs17817449 with obesity in PCOS women, the allele frequencies for T and G in PCOS women were, respectively, 48% and 52%, different from our findings [40].…”
Section: Discussioncontrasting
confidence: 99%
“…In 2016, 13% of adults worldwide had obesity and 39% of people were overweight 1 .The (BMI) is a method of evaluating an adult's weight status based on the weight in kilograms (kg) divided by the square of height in meters (m 2 ), is the most frequently used indicator in social science research to assess obesity [2][3] . Further assessment of the distribution of body fat can be done by evaluating the waist circumference (WC) and the (WHR) which represent what is known as central or abdominal obesity, both of which are significant predictors in young and middle-aged adults as compared to older people and those with low BMI 4 . The worldwide obesity epidemic has contributed to cardiovascular issues such as hypertension, dyslipidemia, and vascular dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…The etiopathology of obesity has been linked to a number of risk factors, including both genetic and environmental ones 3 . One of these factors is oxidative stress, which by promoting the buildup of white adipose tissue and altering food intake, can promote obesity and its accompanying comorbidities 4 .There is a significant direct correlation between oxidative stress indicators and Body Mass Index (BMI).Numerous in vitro studies have demonstrated that elevated oxidative stress and reactive oxygen species stimulate adipocyte proliferation, differentiation and growth as well as control hunger and satiety responses 5 .Oddly, obesity and oxidative stress are linked because too much fat accumulation can lead to an inflammatory and oxidative state via a number of cellular and metabolic pathways 6 .When (BMI) is 30 or more, the person is considered obese 7,8 .A diagnosis of overweight is indicated by a BMI between 25 and 30. With 62% of adults being categorized as obese or overweight 9 , obesity raises inflammatory cytokines and the likelihood of endothelial cell dysfunction .Patients' risk for diabetes and cardiovascular disease (CVD) is increased by metabolic syndrome 10 .…”
Section: Introductionmentioning
confidence: 99%